Deep neck infections and abscess: case series and up to date commentary - Karapantzos, Ilias; Karapantzou, Chrysa; Zarogoulidis, Paul; Karanikas, Michail; Thomaidis, Vasilis; Tsiouda, Theodora (Annals of Research Hospitals, 2017)
Deep neck space infection (DNSI) is defined as infection in the potential spaces and fascial planes of the neck. It has been observed that recognition of DNSI is challenging due to the complex head and neck anatomy. The following five factors are the most important to be considered. Firstly, clinical presentation: management of a compromised airway is the priority. Clinical history and examination. Secondly: laboratory investigations along with computed tomography (CT) imaging in most cases. Thirdly the antibiotics used. Fourthly: treatment in children lacking indications for surgical intervention, therefore a 48-hour trial with of intravenous antibiotics (IV Abx) is firstly commenced. Fifth, surgical intervention: most important indications include signs of airway compromise, no clinical improvement after 48 hours of IV administration. Conservative and surgical approach is viable treatment options and may complement each other.